(untitled) - Braess, Dietrich (Cambridge, 2001)
In this thoroughly revised version of the successful first edition, the author has added new material that will prove useful for research or application of the finite element method. The most important application of finite elements is the numerical solution of elliptic partial differential equations. The author provides thorough coverage of this subject and includes aspects such as saddle point problems that require a more in-depth mathematical treatment.
Keywords: Finite element method,Elasticity,Phương pháp phần tử hữu hạn,Tính đàn hồi; Mathematical models,Mô hình toán học